Model Identitas Peran Kreatif-Suatu Tinjauan Pemahaman Organisasi terhadap Terbentuknya Kreatifitas Karyawan - Rachmawati, Veronika (Kajian Manajemen dan Bisnis, 2009)
This research is empire that teaching the relationship in between of self identity with creativity in working place. The purpose of this research is for testing the identity and creative behavior in working place that is related with theory of identity past and theory about organizational creativity. Model of creative identity is a model that is used to explain two important issue,the first is whether the factors that related with desire for specific part identity influences significant to the activity. The second is whether it got the influence for significant in between of creative identity with the work of employee creative.